2010
DOI: 10.1152/ajpgi.00502.2009
|View full text |Cite
|
Sign up to set email alerts
|

ABCG5/ABCG8-independent biliary cholesterol excretion in lactating rats

Abstract: Lactation is associated with increased expression of bile acid transporters and an increased size and hydrophobicity of the bile acid pool in rats. ATP-binding cassette (ABC) transporters multidrug resistance protein 2 (Mdr2), Abcb11 [bile salt export pump (Bsep)], and Abcg5/Abcg8 heterodimers are essential for the biliary secretion of phospholipids, bile acids, and cholesterol, respectively. We investigated the expression of these transporters and secretion of their substrates in female control and lactating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Abcg5 and Abcg8 show decreased levels of mRNA expression in the liver and ileum. A decrease in the concentration of active Abcg5/Abcg8 heterodimer in the intestine would be expected to yield an increase in net cholesterol uptake through decreased efflux from the enterocyte into the gut lumen, while decreased hepatic expression would minimize cholesterol secretion into bile [ 51 ]. The decreased expression of Abcg5/g8 mRNA in the liver, together with increased expression of cholesterol synthetic genes, likely serve to enhance conservation of cholesterol to allow for sufficient transfer of cholesterol into the milk and for synthesis of bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Abcg5 and Abcg8 show decreased levels of mRNA expression in the liver and ileum. A decrease in the concentration of active Abcg5/Abcg8 heterodimer in the intestine would be expected to yield an increase in net cholesterol uptake through decreased efflux from the enterocyte into the gut lumen, while decreased hepatic expression would minimize cholesterol secretion into bile [ 51 ]. The decreased expression of Abcg5/g8 mRNA in the liver, together with increased expression of cholesterol synthetic genes, likely serve to enhance conservation of cholesterol to allow for sufficient transfer of cholesterol into the milk and for synthesis of bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…However, significant induction of cholesterol biliary secretion in our treated controls and its reduction in BDO‐P5 suggest another mechanism. Indeed, several authors recently demonstrated that modulation of cholesterol biliary excretion is not necessarily associated with changed expression of these transporters 28–31 . Oude Elferink et al 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several authors recently demonstrated that modulation of cholesterol biliary excretion is not necessarily associated with changed expression of these transporters. [28][29][30][31] Oude Elferink et al 32 showed that the main driving force for the secretion of cholesterol into bile is biliary secretion of bile acids. We, therefore, hypothesize that changes in cholesterol biliary excretion in our study are attributable to the corresponding decrease (BDO-P5 group) or increase (control pravastatin group) in bile acid biliary secretion and bile flow through modulation of Bsep.…”
Section: Discussionmentioning
confidence: 99%
“…Single-pass rat liver perfusion was performed as previously described ( 15 ). Mice were anesthetized with urethane (1g/kg ip).…”
Section: Isolated Perfused Liver Preparationmentioning
confidence: 99%